Osmoadaptive GLP-1R signalling in hypothalamic neurones inhibits antidiuretic hormone synthesis and release - Michael P. Greenwood; Mingkwan Greenwood; Soledad Bárez-López; Joe W. Hawkins; Katherine Short; Danijela Tatovic; David Murphy (Elsevier, 2023)
Objectives: The excessive release of the antidiuretic hormone vasopressin is implicated in many diseases including cardiovascular disease, diabetes, obesity, and metabolic syndrome. Once thought to be elevated as a consequence of diseases, data now supports a more causative role. We have previously identified CREB3L1 as a transcription factor that co-ordinates vasopressin synthesis and release in the hypothalamus. The objective here was to identify mechanisms orchestrated by CREB3L1 that co-ordinate vasopressin release. Methods: We mined Creb3l1 knockdown SON RNA-seq data to identify downstream target genes. We proceeded to investigate the expression of these genes and associated pathways in the supraoptic nucleus of the hypothalamus in response to physiological and pharmacological stimulation. We used viruses to selectively knockdown gene expression in the supraoptic nucleus and assessed physiological and metabolic parameters. We adopted a phosphoproteomics strategy to investigate mechanisms that facilitate hormone release by the pituitary gland. Results: We discovered glucagon like peptide 1 receptor (Glp1r) as a downstream target gene and found increased expression in stimulated vasopressin neurones. Selective knockdown of supraoptic nucleus Glp1rs resulted in decreased food intake and body weight. Treatment with GLP-1R agonist liraglutide decreased vasopressin synthesis and release. Quantitative phosphoproteomics of the pituitary neurointermediate lobe revealed that liraglutide initiates hyperphosphorylation of presynapse active zone proteins that control vasopressin exocytosis. Conclusion: In summary, we show that GLP-1R signalling inhibits the vasopressin system. Our data advises that hydration status may influence the pharmacodynamics of GLP-1R agonists so should be considered in current therapeutic strategies.